Evaluating the Impact of Housing Status on Gonorrhea and Chlamydia Screening in an HIV Primary Care Setting. Issue 3 (March 2019) - Clemenzi-Allen, Angelo Asa; Hartogensis, Wendy; Cohen, Stephanie E.; Gandhi, Monica; Geng, Elvin; Christopoulos, Katerina
Abstract : Introduction: Gonorrhea and chlamydia (GC/CT) testing falls below recommended rates for people living with HIV (PLWH) in routine care. Despite evidence that homelessness and unstable housing (HUH) negatively impacts clinical outcomes for PLWH, little is known about GC/CT screening for HUH-PLWH in routine care. Methods: Using an observational cohort of PLWH establishing care at a large publicly funded HIV clinic in San Francisco between February 2013 and December 2014 and with at least 1 primary care visit (PCV) before February 2016, we assessed GC/CT testing for HUH (staying outdoors, in shelters, in vehicles, or in places not made for habitation in the last year) compared with stably housed patients. We calculated (1) the odds of having GC/CT screening at a PCV using logistic regression with random effects to handle intrasubject correlations and (2) the percent of time enrolled in clinical care in which patients had any GC/CT testing ("time in coverage") based on 180-day periods and using linear regression modeling. Results: Of 323 patients, mean age was 43 years, 92% were male, 52% were non-Latino white, and 46% were HUH. Homeless and unstably housed PLWH had 0.66 odds of GC/CT screening at a PCV than did stably housed patients (95% confidence interval, 0.44–0.99; P = 0.043). Time in coverage showed no difference by housing status (regression coefficient, −0.93; 95% confidence interval, −8.02 to 6.16; P = 0.80). Conclusions: Homeless and unstably housed PLWH had 34% lower odds of GC/CT screening at a PCV, demonstrating a disparity in routine care provision, but similar time in coverage. More research is needed to effectively increase GC/CT screening among HUH-PLWH.